HELICOPTER PROCEDURE DESIGN FOR AIR TRAFFIC MOVEMENT IMPROVEMENT: A CASE OF KERTAJATI INTERNATIONAL AIRPORT - Sugiarto, Diko Bagus; Sinaga, Togi Adnan Maruli; Fachrudin, Dedy; Sadiatmi, Rini; Arti, Endang Sugih; Amir, Elfi (Journal of Airport Engineering Technology (JAET), 2024)
A review of Aeronautical Information Publication Indonesia Volume II indicates a critical infrastructure deficiency at Kertajati International Airport. The absence of a designated helipad presents a significant obstacle for air traffic controllers. This research proposed helicopter procedures designed for instrument flight rules to improve air traffic movement at Kertajati International Airport. A qualitative approach using interviews and document analysis was employed. The research identified a critical omission: the absence of designated helicopter take-off and landing locations. This lack of a framework hinders safe and efficient traffic management. The proposed procedure addresses this challenge by providing a structured approach for managing mixed rotary-wing and fixed-wing traffic, potentially reducing human error and delays, and fostering informed decision-making by air traffic controllers.